Direct interaction of Syk and Lyn protein tyrosine kinases in rat basophilic leukemia cells activated via type I Fc epsilon receptors - Amoui, M; Dráberová, L; Tolar, P; Dráber, P (European journal of immunology, 1997)
Activation of rat mast cells through the receptor with high affinity for IgE (Fc epsilonRI) requires a complex set of interactions involving transmembrane subunits of the Fc epsilonRI and two classes of nonreceptor protein tyrosine kinase (PTK). the Src family PTK p53/p56(lyn) (Lyn) and the Syk/ZAP-family PTK p72(syk) (Syk). Early activation events involve increased activity of Lyn and Syk kinases and their translocation into membrane domains containing aggregated Fc epsilonRI, but the molecular mechanisms responsible for these changes have remained largely unclear. To determine the role of Fc epsilonRI subunits in this process, we have analyzed Syk- and Lyn-associated proteins in activated rat basophilic leukemia (RBL) cells and their variants deficient in the expression of Fc epsilonRI beta or gamma subunits. Sepharose 4B gel chromatography of postnuclear supernatants from Nonidet-P40-solubilized antigen (Ag)- or pervanadate-activated RBL cells revealed extensive changes in the size of complexes formed by Lyn and Syk kinases and other cellular components. A fusion protein containing Src homology 2 (SH2) and SH3 domains of Lyn bound Syk from lysates of nonactivated RBL cells; an increased binding was observed when lysates from Ag- or pervanadate-activated cells were used. A similar amount of Syk was bound when lysates from pervanadate-activated variant cells deficient in the expression of Fc epsilonRI beta or gamma subunits were used, suggesting that Fc epsilonRI does not function as the only intermediate in the formation of the Syk-Lyn complexes. Further experiments have indicated that Syk-Lyn interactions occur in Ag-activated RBL cells under in vivo conditions and that these interactions could involve direct binding of the Lyn SH2 domain with phosphorylated tyrosine of Syk. The physical association of Lyn and Syk during mast-like cell activation supports the recently proposed functional cooperation of these two tyrosine kinases in Fc epsilonRI signaling.
Keywords: signální transdukce; Signal Transduction; fosfoproteiny; Tumor Cells, Cultured; prekurzory enzymů; Basophils; Protein Binding; intracelulární signální peptidy a proteiny; Phosphotyrosine; src-Family Kinases; fosfotyrosin; krysa rodu Rattus; agregace receptorů; tyrosinkinasy; zvířata; Enzyme Activation; beta-N-Acetylhexosaminidases; nádorové buňky kultivované; receptory IgE; Mast Cells; Intracellular Signaling Peptides and Proteins; beta-N-acetylhexosaminidasy; Receptor Aggregation; Protein-Tyrosine Kinases; Leukemia, Basophilic, Acute; Receptors, IgE; Syk Kinase; vazba proteinů; akutní bazofilní leukemie; Rats; mastocyty; kinasa Syk; Animals; aktivace enzymů; Phosphoproteins; Enzyme Precursors; bazofily; skupina kinas odvozených od src-genu